Damage of the Cochlear Duct in Guinea Pigs after Direct Administration of SM-Complex - Kawamoto, Kazutomo; Kaneko, Yutaka; Terayama, Yoshihiko; Kasazima, Kazuko; Ise, Ikuo (AUDIOLOGY JAPAN, 1973)
After injection of a high dosis of SM-complex into perilymph, many severe, injuries that could not be found obviously by the systemic administration of SM were observed in tissues in the cochlear duct. The authors defined these injured areas and disclosed the restoration mechanisms about the barriers between perilymph and endolymph. The endolymphatic surface of scala media of those injured areas were covered with one layer of new epithelial cell which was ranged with the epithelial cell layer of Reissner's membrane.